Evaluating the right of healthcare workers to strike as essential workers - Ntlama, Ramasela Johanna (My University, 2025)
Globally, doctors and nurses play an important role in the provision of healthcare. Nurses are the backbone of the medical profession. Although it is everyone’s constitutional right to strike, this is a limited right for healthcare workers, because they are essential workers. From the standpoint of the employees, the ability to strike is essential to the collective bargaining system and positive working relationships. Since the right to strike is essential to the existence of meaningful collective bargaining, strikes and other forms of industrial action play a critical role in the process. When essential workers go on strike without the Essential Service Committee providing minimum service, patients' fundamental rights to healthcare services as outlined in the Constitution in sections 27 and 10, their right to dignity, and their right to life as affirmed in section 11 are all violated. There are ethics that govern the healthcare professionals, and if not followed can result in penalties. The study employed a qualitative approach. Literature review was done to evaluate the right of healthcare workers to strike. Regarding the attitude of healthcare workers towards strike, not all of them are in favour of the strike but engage because of fear for their life’s and threats from colleagues. It also evaluates the attitude of patients towards healthcare workers. There is an increasing concern about the relationship between healthcare workers and their patients. Literature has shown that the members of the public sometimes attack healthcare workers, that is why during strike they do not think twice to leave the patients. What is worrying is leaving the patient unattended and the number of deaths during a strike. The government must come up with minimal requirements during strike so other healthcare workers continue to render service during the strike.
Thesis ( LLM. (Labour Law)) -- University of Limpopo, 2025
Keywords: Collective bargaining; Healthcare workers; Patients’ rights strike; Trade unions; Essential workers; Collective bargaining -- Health care workers; Right to strike; Medical personnel; Labor unions